Yahoo奇摩 網頁搜尋

  1. Q: Simplify the following expression . {[1-(1/n)]/n - (1+n)[1-(1/n)]} x 1/[n-(1/n)] Sol: {[1-(1/n)]/n - (1...

    分類:科學及數學 > 數學 2008年01月16日

  2. ------------------------------------- 圖片參考:http://i.imgur.com/eJdnrq3.jpg

    分類:科學及數學 > 數學 2013年06月11日

  3. 5m-5-2(m+1) =5m-5-2m-2 =3m-7 1st: Multiply out the bracket -2(m+1)= -2m-2 Then the whole expression became 5m-5-2m-2 After that: 5m-2m = 3m -5-2= -7 Therefore the final answer is: 3m-7 Is this help??

    分類:科學及數學 > 數學 2007年09月03日

  4. 1. 2,9,16,23 a) next 3 terms b) use an algebraic expression to respresent the general term of the sequences. 1st term=2 common different=7...

    分類:科學及數學 > 數學 2008年11月16日

  5. 3.Rayond deposits an amount of money in a bank at an interest rate of 5% p.a.. The bank chargs him $50 and he gets back $10950 two years later. Find the amount that he deposits in a bank. Let the amount that he deposits...

    分類:科學及數學 > 數學 2006年10月25日

  6. Γ(z)Γ(1-z)=π/sin(πz)Part 1: Γ(z)= 2∫[0~∞] x^(2z-1)exp(-x^2) dx Γ(z) = ∫[0~∞] t^(z-1)exp(-t) dx (Let t=x^2) = 2∫[0~∞] x^(2z-1)exp(-x^2) dx Part 2: Γ(z)Γ(1-z)= 2∫[0~π/2] tan^(1-2z) dθ Γ(z)Γ(1-z) ={2∫[0~∞] x^(2z-1)exp(-x^2) dx}{2...

    分類:科學及數學 > 數學 2010年12月29日

  7. (1-y+3y^2)^3 =[1-y(1+3y)]^3 =(1)(1)-3(y)(1+3y)+3(y^2)(1+3y)^2-(y^3)(1+3y)^3 =1-3y+12y^2-19y^3+....// 2008-07-03 16:07:08 補充: (1-y+3y^2-12y^3)^3 =1-3y+12y^2-55y^3+....// 2008-07-07 19:08:26 補充: (1-y+3y^2-12y^3)^3 =-1728y^9+1296y^8-756y^7+675y^6-279y^5+108y^4-55y^3+12y^2-3y+1

    分類:科學及數學 > 數學 2008年07月12日

  8. 1.6/(x^2-9)-2/(x^2-1) 2.2/(a^2+4a+3)-2/(a^2+6a+8) 3.2/(a^2-1)-2(a^4+2a^2+6)/(a^6+a^4+a^2+1)

    分類:科學及數學 > 數學 2008年02月24日

  9. Find An Expression For 'a' if a^b=b^c a=b^(c/b)

    分類:科學及數學 > 數學 2013年08月28日

  10. Perimeter of the equilateral triangle = 3y cm Perimeter of the square = 4(3y) cm = 12y cm 3y + 12y = 105 15y = 105 y=7

    分類:科學及數學 > 數學 2007年01月17日

  1. 相關詞

    expression